METAPHYSICS, THE ABSOLUTE AND THE HOMONIMY OF THE NEGATIVE. PROLEGOMENA FOR A SPECULATIVE LOGIC. PART I - Horațiu Marius TRIF-BOIA (Studia Universitatis Babeș-Bolyai. Philosophia, 2018)
Our paper addresses eight main and traditional issues of Philosophy: the issue of speculative logic; the issue of the fundamental premises of existence and thinking — which engages on the path of absolute ontological reduction; the issue of absolute Nothingness revealed as the ultimate result of the previous reduction; the issue of the realness and effectiveness of Nothingness; the issue of ontological Difference; the issue of the consistency and apodicticity of metaphysics; the issue of the nature of the Absolute; and the issue of the Ontological Argument. The results that we gained at the end of our work show that the ontological Ground is the Absolute and that the Absolute is the transcendent instance of immediate identity of irreducible opposites. This instance is consistent with the traditional claims of philosophical and theological metaphysics and it supports the Ontological Argument through the overcoming of the formal logic principles.